2020
DOI: 10.1515/remav-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

Co-Integration Test of Selected Indexes on the Share Market and Index of Housing Real Estate Prices

Abstract: The integration of financial markets is an ongoing process throughout the world. Research shows that, from Australia through Europe to the United States, the capital and real estate markets are integrating, influencing each other. Although this process seems obvious, only research can show whether it actually occurs. Identifying these relationships is important for analyzing the entire market. Many methods, such as estimating the cost of equity, have been developed with the stock market in mind. Meanwhile, rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Furthermore, Oikarinen (2006) laid out the possibility of a negative causal relationship between house prices and stock prices due to house markets being driven by local factors whereas global factors drive stock prices. Apergis and Lambrinidis (2007) and Wolski (2020) are one of the few authors who incorporated the conventional method of cointegration for house markets and stock markets. Apergis and Lambrinidis (2007) remarked an integration of both the stock markets and unsecuritized real estate markets in addition to the wealth effects for both the UK and the US.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Oikarinen (2006) laid out the possibility of a negative causal relationship between house prices and stock prices due to house markets being driven by local factors whereas global factors drive stock prices. Apergis and Lambrinidis (2007) and Wolski (2020) are one of the few authors who incorporated the conventional method of cointegration for house markets and stock markets. Apergis and Lambrinidis (2007) remarked an integration of both the stock markets and unsecuritized real estate markets in addition to the wealth effects for both the UK and the US.…”
Section: Introductionmentioning
confidence: 99%
“…Apergis and Lambrinidis (2007) remarked an integration of both the stock markets and unsecuritized real estate markets in addition to the wealth effects for both the UK and the US. Wolski (2020) extrapolated cointegration results for the seven Polish cities. He implemented the Engle-Granger (1987) test from the third quarter of 2006 to the fourth quarter of 2018 and found that there was little or no case of cointegration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation